2007
DOI: 10.1002/ejic.200601052
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of the Electronic Structure and Spectroscopic Properties of [Ru(Htcterpy)(NCS)3]3–

Abstract: The ground-and excited-state structures of [Ru(Htcterpy)-(NCS) 3 ] 3-(1H) (tcterpy = 4,4Ј,4ЈЈ-tricarboxy-2,2Ј:6Ј,2ЈЈ-terpyridine) are optimized by the DFT and CIS methods, respectively. Absorption and emission spectra in the gas phase and in solution (ethanol and water) are predicted at the TD-DFT/ B3LYP level. Experimental spectra are roughly reproduced by our calculated results. In ethanol solution, the HOMOs of the absorption spectra are dominated by d orbitals of the ruthenium atom and thiocyanate ligands,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 54 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…20 Recently it was proposed that several transitions may be involved in the 1 MLCT absorption bands of Ru(II) complexes, such as dp(Ru) / p*(bpy) and dp(Ru) / p*(bpy(C^C-Ph)). 40,41 Our DFT/TDDFT calculations support this assignment (vide infra).…”
Section: Steady State Absorption Spectrasupporting
confidence: 66%
See 2 more Smart Citations
“…20 Recently it was proposed that several transitions may be involved in the 1 MLCT absorption bands of Ru(II) complexes, such as dp(Ru) / p*(bpy) and dp(Ru) / p*(bpy(C^C-Ph)). 40,41 Our DFT/TDDFT calculations support this assignment (vide infra).…”
Section: Steady State Absorption Spectrasupporting
confidence: 66%
“…This assumption is consistent with a recent theoretical investigation on Ru(II) polypyridine complexes. 40,41,59 Complex 3 shows a long lifetime of 58.4 ms, indicating that the emissive state is not the typical 3 MLCT state. The transient absorption demonstrated that the long-lived excited state is pyrene-based, we propose that the excited triplet state is 3 IL/ 3 LLCT state (Scheme 3 and Table 3).…”
Section: Transient Absorption Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…This could be probably due to more charge transfer to the LUMO orbitals for these dyes as compared to black dye. In the LUMO orbitals of these complexes, the electron density distributions mainly located on H 3 tctpy ligand, while for black dye it is only ascribed to the centre pyridine of H 3 tctpy [31]. As compared to the black dye-sensitized solar cell, the mLBD dyes showed higher current densities, which could be probably because of their increased incident photon to-current conversion efficiencies spectra.…”
Section: Thermal Stabilitymentioning
confidence: 94%
“…Recently density function theory (DFT) and time dependent DFT (TDDFT) calculations have been successfully used in the study of luminescent organic materials and transitional metal complexes [28][29][30][31]. The understanding of the photophysical properties can be improved with these calculations, especially the information of the low-lying excited states.…”
Section: Dft/tddft Calculations On the Singlet And Triplet Excited Stmentioning
confidence: 99%